PENGHAPUSAN THRIFTING IMPOR SHOP SEBAGAI UPAYA PENEGAKAN PERATURAN MENTERI PERDAGANGAN NOMOR 40 TAHUN 2022 - Safitri, Nadila; Bakhtiar, Handar Subhandi (TANJUNGPURA LAW JOURNAL, 2024)
Abstract  The existence of a Thrifting Import Shop business is getting stronger in Indonesia. Based on data submitted by the Central Statistics Agency, imports of used clothing experienced an increasing trend in 2022 with a percentage of 26.22 percent and the value of imports of $ 272,146 from the previous year. Whereas this business accords with the Regulation of the Minister of Trade of the Republic of Indonesia Number 40 of 2022 concerning Amendments to the Regulation of the Minister of Trade Number 18 of 2021 concerning Goods Prohibited Exports and goods are prohibited from imports are illegal business activities. Therefore, the urgency and concept of the elimination of the import of imports shops as a form of law enforcement efforts for the Minister of Trade Regulation of the Republic of Indonesia Number 40 of 2022 concerning Amendments to the Regulation of the Minister of Trade Number 18 of 2021 concerning goods prohibited from exports and goods are prohibited from imports into problems that will be discussed in the study This. The purpose of the study is to analyze the urgency and concept of elimination of the import of import shops in Indonesia. The research method used is normative juridical with statute, conceptual, and comparative approaches. The results of the analysis from this study indicate that the elimination of the import of imports indeed needs to be done because it has a negative impact as issues of environmental damage, human health, threatening the existence of MSMEs, and harming the country through the loss of tax income. In addition, the elimination of the import of import shop business also aims to protect domestic textile workers. The concept of eliminating the business Thrifting Import Shop is to implement a policy of providing business subsidies. Also, this can be a win-win solution for law enforcement, and people who have been entrepreneurs in the field of thrifting imports do not lose their livelihoods and still earn income. It can even develop its business.Abstrak  Eksistensi usaha thrifting impor shop semakin menguat di Indonesia. Berdasarkan data yang disampaikan oleh Badan Pusat Statistik, impor pakaian bekas mengalami tren kenaikan pada tahun 2022 dengan persentase 26,22 persen dan nilai impor $272.146 dari tahun sebelumnya. Padahal usaha ini menurut Peraturan Menteri Perdagangan Republik Indonesia Nomor 40 Tahun 2022 tentang Perubahan atas Peraturan Menteri Perdagangan Nomor 18 Tahun 2021 tentang Barang Dilarang Ekspor dan Barang Dilarang Impor merupakan kegiatan usaha yang ilegal. Oleh karena itu urgensi dan konsep penghapusan usaha thrifting impor shop sebagai bentuk upaya penegakan hukum Peraturan Menteri Perdagangan Republik Indonesia Nomor 40 Tahun 2022 tentang Perubahan atas Peraturan Menteri Perdagangan Nomor 18 Tahun 2021 tentang Barang Dilarang Ekspor dan Barang Dilarang Impor menjadi permasalahan yang akan dibahas dalam penelitian ini. Tujuan dari penelitian ini adalah untuk menganalisis urgensi dan konsep penghapusan usaha thrifting impor shop di Indonesia. Metode penelitian yang digunakan adalah yuridis normatif dengan pendekatan peraturan perundang-undangan, pendekatan konseptual, dan pendekatan komparatif. Hasil analisis dari penelitian ini menunjukkan bahwa penghapusan usaha thrifting impor shop memang perlu dilakukan karena memiliki dampak negatif seperti isu tentang kerusakan lingkungan, kesehatan manusia, mengancam keberadaan UMKM, dan merugikan negara melalui hilangnya pendapatan pajak. Selain itu, penghapusan usaha thrifting impor shop ini juga bertujuan untuk melindungi pekerja tekstil dalam negeri. Adapun konsep penghapusan usaha thrifting impor shop adalah dengan memberlakukan kebijakan pemberian subsidi usaha. Hal ini juga dapat menjadi win-win solution di mana hukum dapat ditegakkan dan masyarakat yang telah berwirausaha di bidang thrifting impor shop tidak kehilangan mata pencahariannya dan tetap mendapat penghasilan. Bahkan juga dapat mengembangkan usahanya.